2004
DOI: 10.1021/jp038048x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Simulation Studies of the Orientation and Conformation of Cytochrome c Adsorbed on Self-Assembled Monolayers

Abstract: Cytochrome c (Cyt-c) is an important membrane electron-transfer protein. To maximize its electron transfer, adsorbed Cyt-c should have a preferred orientation with its heme ring close and perpendicular to the surface. Moreover, the adsorbed Cyt-c should keep its native conformation. In this work, the orientation and conformation of Cyt-c adsorbed on carboxyl-terminated self-assembled monolayers (SAMs) are investigated by a combined Monte Carlo and molecular dynamics simulation approach. The root-mean-square de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
219
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(247 citation statements)
references
References 71 publications
28
219
0
Order By: Relevance
“…However, a recent study (Utesch et al 2013) reporting a titration curve of an amino-terminated alkanethiol SAM showed that the level of ionization was very sensitive at pH values around 6 (with 16 ± 5% protonation at pH 7 and 52 ± 9% at pH 6). A positive correlation between the ionization level of a SAM and the strength of adsorption of charged proteins was found (Zhou et al 2004;Utesch et al 2013). Therefore, it is crucial to compute and model the surface ionization to obtain reliable results compatible with experiments.…”
Section: Ionization and Hydrationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a recent study (Utesch et al 2013) reporting a titration curve of an amino-terminated alkanethiol SAM showed that the level of ionization was very sensitive at pH values around 6 (with 16 ± 5% protonation at pH 7 and 52 ± 9% at pH 6). A positive correlation between the ionization level of a SAM and the strength of adsorption of charged proteins was found (Zhou et al 2004;Utesch et al 2013). Therefore, it is crucial to compute and model the surface ionization to obtain reliable results compatible with experiments.…”
Section: Ionization and Hydrationmentioning
confidence: 99%
“…Therefore, it is crucial to compute and model the surface ionization to obtain reliable results compatible with experiments. The protonation states of SAMs in modeling studies are mostly represented by random assignment of protonated and deprotonated groups (Alvarez-Paggi et al 2013;Utesch et al 2012;Zhou et al 2004). In several studies, they are represented either by a uniform distribution of small partial charges (Sun et al 2005) or by large partial charges being assigned to functional groups in neutral surfaces (Wang et al 2010b).…”
Section: Ionization and Hydrationmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Also, the observation of such potential suggests that there is no change in the protein conformation in consequence of the SAM-Cyt c molecular recognition process. 32,33 Based on the Nicholson's method, 34 the dependence of the difference between the anodic and cathodic peak potentials ( E p ) on the scan rate allows one to estimate the kinetic parameter, . Based on equation 3 with f = F/RT, the heterogeneous electron transfer rate constant, k 0 , was determined from the slope of the curve presented in the plot of 2 vs. the reciprocal of the scan rate, v -1 (Figure 3c).…”
Section: Electroactivity Of the Hpyt Sammentioning
confidence: 99%
“…This difficulty has been overcome by using electrode modifiers such as metal oxides, advanced carbon materials, DNA or lipid membranes [20][21][22][23][24][25][26] . In particular, the modification of surfaces with organic thin films like self-assembled monolayers (SAM), has been extensively used to manipulate the electrode surface, promoting the appropriate orientation of the protein and thus enhancing its electroactivity [27][28][29][30][31][32][33][34][35][36] .…”
Section: Introductionmentioning
confidence: 99%